What drives tourists to return? The mediating role of tourist satisfaction - Muhammad Saputra; Novita Sari; Fazlida Mohd Razali; Lis Linda Wati; Sumaria Liswita; Herlina Hikmani (Jurnal Fokus Manajemen Bisnis, 2026)
To measure the intensity of tourist behavior, tourist attractions, infrastructure, and local cuisine as initial stimuli influencing tourist satisfaction and the final decision to revisit. Lampung, Indonesia, located at the southern gateway of Sumatera, has strong tourism potential supported by diverse natural attractions, cultural heritage, and local wisdom. This study examines the influence of tourist attractions, infrastructure, and local cuisine on tourists’ intention to revisit, with tourist satisfaction as a mediating variable. A quantitative causal-associative design was applied, involving 150 domestic tourists selected through purposive sampling. Data were analyzed using structural equation model-partial least square. The results show that tourist attractions, infrastructure, and local cuisines significantly affect revisit intention. Tourist satisfaction also has a significant positive effect and mediates the relationships between destination attributes and revisit intention. These findings indicate that positive destination experiences enhance satisfaction, which in turn strengthens the intention to revisit. The study contributes to the tourism literature by confirming the mediating role of tourist satisfaction in the relationship between destination attributes and behavioral intentions. Practically, stakeholders should improve attractions, infrastructure, and culinary experiences to enhance satisfaction and support sustainable tourism development.